Optic Neuropathy Secondary to Linezolid for Multidrug-resistant Mycobacterial Tuberculosis: Poster Presentation - Case Series - Ophthalmologist - ARSI NOVIANA SARI; Ika Nuraita (Ophthalmologica Indonesiana, 2024)
Abstract Introduction : Toxic optic neuropathy is well known side effect of medications, including linezolid in patients with MDR-TB. We present 2 cases of patients with linezolid associated ON. Case Illustration : A 28 year pld man (case 1) and a 50 year old woman complained bilateral progressive visual loss after long term use of linezolid (both 8 months). On initial visit, case 1 presented with 0.1 visual acuity and case 2 presented with counting finger visual acuity. Both have hyperemic optic disc. OCT showed optic disc edema. Both patients showed generalized visual field defect on the Humphrey test. We immediately stopped the linezolid treatment. Discussion : The exact mechanism of linezolid induced ON is still unclear. It may be caused by impaired mitochondrial function for adenosine triphosphate (ATP) synthesis within retinal nerve fiber layer. Duration of linezolid therapy affects the prognosis for linezolid ON. Conclusion : Both Ophthalmologist and Physicians must be aware that visual function monitoring and early recognition of toxicity linezolid. Immediate cessation of linezolid has favorable visual recovery